Editorial [Hot Topic: Heterocyclic Chemistry (Guest Editor: Jan Bergman) ] - Bergman, Jan (Current Organic Chemistry, 2008)
Aziridines constitute a reactive and versatile class of molecules and in the present review Dr Chebanov and his co-workers form the National Academy of Science of Ukraine in Kharkiv demonstrate have useful the subclass C-acylated aziridines can be. Compounds with triazepine skeletons have attracted considerable attention due their interesting biological properties. The subclass triazepandiones has now been reviewed in depth by Drs G. Léna and G. Guichard form the Institute of Molecular and Cell Biology, Strasbourg, France. The use of microwaves is becoming more and more frequent and Drs S. Bajaj and R. Jindal from the College of Pharmacy, Ram Nagar, India have contribute a review featuring applications of microwaves in the synthesis of bioactive heterocycles. Prof. M. Sollner, from the University of Ljubljana, Slovenia, has contributed to this journal previously and now she is coming back, together with Dr Z. Jakopin with a comprehensive review on 1,2,4 and 1,2,4-oxadiazoles.